Non-Sterile Clean Gloves versus Sterile Gloves for Uncomplicated Wound and Laceration Repair: A Systematic Review of Clinical, Economic, and Patient-Reported Outcomes - Regenio Akira Handoyo; John M. Sangkai (The Indonesian Journal of General Medicine, 2025)
Introduction The use of sterile gloves is a deeply entrenched standard of care for surgical procedures, including the repair of cutaneous wounds and lacerations, to prevent surgical site infections (SSIs). However, this practice is resource-intensive and its necessity for minor, non-operating room procedures is increasingly questioned. This review evaluates the clinical and economic rationale for using clean, non-sterile gloves as an evidence-based alternative in outpatient and emergency settings (Hamam et al., 2024; Brewer et al., 2016). Methods A systematic review and meta-analysis was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines. Major electronic databases (PubMed, Embase, Cochrane CENTRAL, and CINAHL) were searched through May 2024 for randomized controlled trials (RCTs) and comparative observational studies comparing sterile versus non-sterile gloves for wound repair (Hamam et al., 2024). The primary outcome was the incidence of SSI. Secondary outcomes (16 total) included cost-effectiveness, procedure duration, and adverse events. Methodological quality was rigorously assessed using the Cochrane Risk of Bias 2 (RoB 2) and Risk of Bias in Non-randomised Studies - of Interventions (ROBINS-I) tools (Mahraoui et al., 2024; Hamam et al., 2024). Results Ten primary studies (6 RCTs, 4 observational) and three systematic reviews, encompassing over 21,000 patients, met the inclusion criteria. The quantitative meta-analysis of RCTs found no statistically significant difference in the incidence of SSI between the non-sterile glove group and the sterile glove group. Pooled data from recent meta-analyses confirm this finding (Risk Ratio 1.17, 95% Confidence Interval [CI] 0.88–1.55, P=.62) (Hamam et al., 2024). This result was highly robust, with no statistical heterogeneity (I² = 0%) (Hamam et al., 2024; Brewer et al., 2016). Evidence from multiple primary studies confirmed that non-sterile gloves are a highly cost-effective option, with sterile gloves costing up to seven times more per pair (Perelman et al., 2004; Mehta et al., 2014). Discussion The aggregated evidence demonstrates high-confidence non-inferiority for the use of clean, non-sterile gloves in uncomplicated, superficial wound repairs in immunocompetent patients (Heal et al., 2015; Zwaans et al., 2022). This is clinically plausible as traumatic lacerations are already contaminated, and a "clean" technique (including sterile instruments) is sufficient to prevent iatrogenic infection. However, the evidence clearly does not support non-sterile glove use for high-risk scenarios, such as in immunocompromised patients (Zwaans et al., 2022) or for complex, deep-tissue reconstructions (Rogues et al., 2007). A significant gap exists in the literature regarding patient-reported outcomes, particularly long-term cosmetic results. Conclusion Clean, non-sterile gloves are a safe, cost-effective, and evidence-based standard of care for the vast majority of uncomplicated laceration and wound repairs performed outside a formal operating room in immunocompetent patients. Clinical guidelines and institutional policies should be updated to reflect this evidence, promoting high-value care and reducing medical waste.